1996
DOI: 10.2105/ajph.86.1.87
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of a severe-weather warning system and disaster preparedness, Calhoun County, Alabama, 1994.

Abstract: Tornado preparedness warning system effectiveness, and shelter-seeking behavior were examined in two Alabama areas after tornado warnings. In the area without sirens, only 28.9% of 194 respondents heard a tornado warning of these, 73.2% first received the warning from radios or television. In the area with sirens, 88.1% of 193 respondents heard a warning, and 61.8% first received the warning from a siren. Knowledge of warnings, access to shelter, and education were key predictors for seeking shelter. Our findi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(55 citation statements)
references
References 6 publications
0
54
1
Order By: Relevance
“…Based on literature in the area of adaptation to climate change (i.e., Norris and Bati 1987, Igoden et al 1988, Lin 1991, Maddison 2006, Deressa et al 2008) and literature on warning response (e.g., Edwards 1993, Farley et al 1993, Liu et al 1996, Balluz et al 2000 we expected that the respondents with more formal education would be able to better access, understand, and interpret warning messages. The results revealed that education did seem to make a difference in this regard when compared to noneducated respondents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on literature in the area of adaptation to climate change (i.e., Norris and Bati 1987, Igoden et al 1988, Lin 1991, Maddison 2006, Deressa et al 2008) and literature on warning response (e.g., Edwards 1993, Farley et al 1993, Liu et al 1996, Balluz et al 2000 we expected that the respondents with more formal education would be able to better access, understand, and interpret warning messages. The results revealed that education did seem to make a difference in this regard when compared to noneducated respondents.…”
Section: Discussionmentioning
confidence: 99%
“…The evidence regarding the particular effect of education on response to warning has been mixed. In general, most studies (Edwards 1993, Farley et al 1993, Liu et al 1996, Balluz et al 2000 have found a positive correlation between education and evacuation (response to warning). Interestingly, Farley et al (1993) find that the lower the education a person has, the more likely they are to 'believe' the warning, though in terms of responding to warning they find a positive correlation with education.…”
Section: Formal Education As a Determinant Of Climate Adaptive Capacitymentioning
confidence: 99%
“…For example, tornado research has shown that understanding the situation and what to do about it (Liu et al 1996; Alberta Public Safety Services 1991) increases an individual's personalization, or perception, of risk (i.e., stage five in the decision-making model). Also, tornado research has identified factors, unrelated to alerts and warnings, shown to increase an individual's perception of risk, and in turn, the likelihood of his/her response.…”
Section: Public Warning Response In Disastersmentioning
confidence: 99%
“…For example, people's knowledge and response to severe thunderstorm and tornado warnings issued by the US National Weather Service have been assessed in Ohio by Wilson (1995), in Alabama by Liu et al (1996) and in Arkansas by Balluz et al (2000). Haque (1997) has studied the impact of tropical cyclone warnings in Bangladesh.…”
Section: Introductionmentioning
confidence: 99%